EVALUTION OF BIOCHEMICAL PARAMETERS OF OFFSPRING OF FEMALE RATS AT DIFFERENT AGES RECEIVING HIGH-PROTEIN, FORTIFIED WITH CALCIUM AND VITAMIN D, DAIRY PRODUCT - Tatyana Petrovna Bondar; Kirill Sergeevich Svetlitskiy; Julia Sergeevna Svetlitskaia; Olga Alexandrovna Aseeva (Наука. Инновации. Технологии, 2022)
Currently, the importance of vitamin D for human body is determined not only by ability to regulate calcium and phosphorus metabolism, processes of osteogenesis and maturation of the skeleton, but also affects the immune system and psychomotor development. The aim of the study was to investigate the effect of high-protein milk product, fortified with calcium and vitamin D in different doses of mineral metabolism in laboratory animals in childhood and adolescence. A biochemical study of 72 Wistar rats in different periods of postnatal ontogenesis. Mineral metabolism was evaluated by content calcidiol, calcium, inorganic phosphorus, calcium-phosphorus ratio, total protein and activity of alkaline phosphatase in serum. It was found that rats not treated milk product is insufficient vitamin D. the necessity of selecting the optimal dose for targeted prevention of hypovitaminosis D. It was shown that rats treated with a milk product enriched with calcium, protein and a therapeutic dose of vitamin D, metabolic disorders was accompanied by a pronounced and prolonged biochemical syndrome, which is not observed in the other groups.